Ultrasound diagnosis of iliac lymph node metastases in cancer of the cervix uteri - Ye. V. Barinova; M. A. Chekalova; Ye. K. Dvorova (ABV-press, 2015)
The Outpatient Ultrasound Diagnosis Group, Research Consulting Department, N. N. Blokhin Russian Cancer Research Center, studied the results of an examination in 93 patients with the verified diagnosis of cancer of the cervix uteri (CCU). To specify the extent of a tumor process, a comprehensive ultrasound examination was made in all the patients with verified CCU during their first visit. Our findings were statistically processed. According to our findings, ultrasound computed tomography is a highly informative method to diagnose retroperitoneal lymph node (LN) metastases, which defines the shape, sizes, structure, location, and number of metastatic LNs. Iliac LNs with reactive changes were detected in 24.7 % of CCU cases. No ultrasound signs of iliac LN metastatic involvement were found in 4.3 % of cases in the presence of CCU micrometastases. The number of metastatic regional LNs was validly proven to increase with larger tumor sizes. The threshold values of cervicaltumors were determined, which may presume the presence or absence of iliac LN metastases to have a rather high sensitivity and specificity. The risk of LN metastatic involvement was validly proven to be 4.1-fold higher with greater two or more threshold values of a cervical tumor.